If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 + x = 5x + -1 + 4 Reorder the terms: -3 + 2x + x = 5x + -1 + 4 Combine like terms: 2x + x = 3x -3 + 3x = 5x + -1 + 4 Reorder the terms: -3 + 3x = -1 + 4 + 5x Combine like terms: -1 + 4 = 3 -3 + 3x = 3 + 5x Solving -3 + 3x = 3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -3 + 3x + -5x = 3 + 5x + -5x Combine like terms: 3x + -5x = -2x -3 + -2x = 3 + 5x + -5x Combine like terms: 5x + -5x = 0 -3 + -2x = 3 + 0 -3 + -2x = 3 Add '3' to each side of the equation. -3 + 3 + -2x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 3 + 3 -2x = 3 + 3 Combine like terms: 3 + 3 = 6 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| 1/2+m=2/3 | | -5/3=x+1/3 | | m+1/4=29/4 | | -9+w=-3 | | -28/5=a-6 | | 1+b=9 | | 4/35=b-2/7 | | 1+m=1/3 | | x+10=29/3 | | n-8/9=-44/9 | | d+3/5=67/45 | | n-8/9=19/9 | | k+4/9=56/45 | | b+7/10=77/10 | | n/2=4/7 | | t/4=-4/5 | | 5+m=0 | | 46/5=b-4/5 | | b-4=-11/3 | | x/5+4=7 | | m-10=-75/8 | | a-1/5=13/60 | | n/2=5 | | -1+n=-3/2 | | n/-6=5 | | k/7=6/7 | | b+5=16 | | 4/5+a=17/15 | | w/7=5/7 | | n+1=5/3 | | n+9/10=119/110 | | 3a=3/2 |